STI Services for Adolescents and Youth in Low and Middle Income Countries: Perceived and Experienced Barriers to Accessing Care - Newton-Levinson, Anna (J Adolesc Health, 2016)
Access to sexual and reproductive health services (SRH) is vital for sexually active adolescents; yet, their SRH care needs are often unmet. We conducted a qualitative systematic review of mixed methods studies to assess adolescent and provider views of barriers to seeking appropriate medical care for sexually transmitted infection (STI) services for adolescents. We searched peer-reviewed literature for studies published between 2001–2014 with a study population of youth (aged 10–24 years) and/or health service providers. Nineteen studies were identified for inclusion from fifteen countries. Thematic analyses identified key themes across the studies. Findings suggest that youth lacked knowledge about STIs and services. Additionally, youth experienced barriers related to service availability and a lack of integration of services. The most reported barriers were related to acceptability of services. Youth reported avoiding services or having confidentiality concerns based on provider demographics and some behaviors. Finally, experiences of shame and stigma were common barriers to seeking care. Adolescents in low and middle income countries experience significant barriers in obtaining STI and SRH services. Improving uptake may require efforts to address clinic systems and provider attitudes, including confidentiality issues. Moreover, addressing barriers to STI services may require addressing cultural norms related to adolescent sexuality.